2010
DOI: 10.1271/bbb.100110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Osthole on Migration and Invasion in Breast Cancer Cells

Abstract: Osthole, a natural coumarin derivative, is extracted from the fruit of Cnidium monnieri Cusson. Breast cancer is one of the most commonly diagnosed cancers and the leading cause of death in women. Recent studies have shown that Osthole has anti-tumor activity. However, the effects of Osthole on the migration and invasion of cancer cells have not yet been reported. Here, we found that Osthole is effective in inhibiting the migration and invasion of breast cancer cells by wound healing and transwell assays. Luci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 22 publications
5
58
0
Order By: Relevance
“…Metastasis is one of the major causes of cancer-related mortality (31)(32)(33)(34)(35). At present, there is an intense effort to identify potential therapeutic agents that inhibit metastasis (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis is one of the major causes of cancer-related mortality (31)(32)(33)(34)(35). At present, there is an intense effort to identify potential therapeutic agents that inhibit metastasis (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is an intense effort to identify potential therapeutic agents that inhibit metastasis (35)(36)(37)(38). We previously demonstrated that CEEF treatment significantly inhibits cell proliferation and induces cell cycle arrest Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental conditions and seasonal changes may affect the incidence of coumarins in various parts of the plant (4). Among coumarins, a number of compounds have been reported to exhibit anticancer properties, including imperatorin (5), esculetin (6) and osthole, which inhibits the migration and invasion of breast cancer cells, potentially via the inhibition of matrix metalloproteinase promoter and enzymatic activity (7). Another type of 4-phenylcoumarins isolated from C. inophyllum is calocoumarin A (8).…”
Section: Calophyllum Inophyllum L (C Inophyllum) Of the Familymentioning
confidence: 99%
“…Osthole ( Figure 1) is a major bioactive ingredient isolated from Cnidium monnieri (L.) cusson [1,2], which has been used for treatment of pain in female genitalia, impotence, and suppurative dermatitis (as an antipruritogenic agent). Osthole exhibits various pharmacological activities, including in vitro/in vivo antitumor effects [3][4][5][6][7][8], alleviation of hyperglycemia and hypolipidemia [9,10], and has been proposed the possibility of its development as a promising lead compound for drug discovery [11,12]. However, the clinical utility of this phytochemical is limited due to its low bioavailability in vivo [13][14][15][16], and some structural modifications are required for sufficient bioavailability upon oral administration.…”
Section: Introductionmentioning
confidence: 99%